The memory of a tree; an interactive visual storytelling installation - Hyunjoo Oh (Journal of Science and Technology of the Arts, 2012)
Over the centuries, people have combined fields, leading to the creation of new domains. For example, artists have used technology to widen the range of their medium to express ideas in new ways. Similarly, technology has leveraged art to expand its range of application. Both art and technology continue to inspire innovation in each other. A contemporary example of this process is evident in interactive art era; this article covers this topic focusing on tangible interface pieces. There have been many compelling demonstrations that involve tangible interaction to increase audience interests through their embodied interaction. However, most existing approaches are limited to engaging a user’s immediate, temporary experience with setting some context of the environment with story elements. This article presents an interactive installation that engages the audience, building an immersive environment based on the synergy between embodied interaction and storytelling in a more active and meaningful way. It is based on the belief that tangible interfaces have the potential to convey narratives more meaningfully based on physical interaction and human senses and fundamentally, aims to supply another potential of tangible interfaces to spark further discussion in this area.